Bacteriologic and Genomic Investigation of Bacillus anthracis Isolated from World War II Site, China - Yarong Wu; Yuan Yuan; Bing Yuan; Jiaxin Li; Jinglin Wang; Yujun Cui (Emerging Infectious Diseases)
Records suggest Bacillus anthracis was used in biowarfare during World War II, but evidence remains limited. We isolated B. anthracis from soil at the remains of a World War II–era laboratory in China. Phenotypic and genomic analyses confirmed the finding, highlighting the value of microbial forensics in biothreat investigation.